2021
DOI: 10.1002/pol.20210448
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical properties and bio‐interfacial interactions of surface modified PDLLA‐PAMAM linear dendritic block copolymers

Abstract: Here, we demonstrate the applicability of self‐assembling linear‐dendritic block copolymers (LDBCs) and their nanoaggregates possessing varied surfaces as therapeutic nanocarriers. These LDBCs are comprised of a hydrophobic, linear polyester chemically coupled to a hydrophilic dendron polyamidoamine (PAMAM)—the latter of which acts as the surface of the self‐assembled nanoaggregate in aqueous media. To better understand how surface charge density affects the overall operability of these nanomaterials, we modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 58 publications
(77 reference statements)
1
5
0
Order By: Relevance
“…As expected, on account of previous investigations [19,[68][69][70], the Zeta potential of self-assembled structures was dependent on the nature of functional end groups of the hydrophilic dendritic domains, forming the nanoparticle surface. Thus, the values obtained for dendrons bearing cationic ammonium groups were highly cationic (39-72 mV), whereas the amphiphilic dendron L1-8 containing anionic carboxyl groups gave rise to negatively charged micelles (−27.2 ± 3.9 mV).…”
Section: Dynamic Light Scattering and Zeta Potentialsupporting
confidence: 84%
“…As expected, on account of previous investigations [19,[68][69][70], the Zeta potential of self-assembled structures was dependent on the nature of functional end groups of the hydrophilic dendritic domains, forming the nanoparticle surface. Thus, the values obtained for dendrons bearing cationic ammonium groups were highly cationic (39-72 mV), whereas the amphiphilic dendron L1-8 containing anionic carboxyl groups gave rise to negatively charged micelles (−27.2 ± 3.9 mV).…”
Section: Dynamic Light Scattering and Zeta Potentialsupporting
confidence: 84%
“…30,39 In contrast, IL-LDBC NPs had a slightly positive to neutral surface charge, which by typical cellular mechanisms would command robust cellular uptake. 40 However, it was observed that IL-LDBCs bypassed the filopodia-mediated uptake observed with unmodified LDBCs 41 or the endolysosomal pathway observed with DNA-coated iron oxide particles, 42 and had a much more delayed uptake, beginning at 180 seconds (Fig. 8B and C).…”
Section: Resultsmentioning
confidence: 94%
“…However, LDBC NPs have a surface charge of ∼+33 mV due to their cationic amine surface, which resulted in a fast uptake process through the cell membrane, as anticipated. 37 However, the second effect driving cellular uptake of NPs was uniquely determined by differences in the compositional assembly of the IL with the PLGA and LDBC polymers. Despite having a surface charge of −60 mV, IL-PLGA NPs penetrated the cell membranes aggressively over time, upending the traditional wisdom that the greater the negative charge, the slower the uptake.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In live cell culture, particles appear to load through filopodial processes, a route seen for polyplexes such as those generated from glycopolymers 78 and other PAMAM-based nanoparticles. 79 Similar to these polymer systems, nanoparticles are trafficked to lysosomal compartments (Figure 8c−e) as observed using LysoTracker (green) to image lysosomes alongside fluorescence associated with the C5 dye. Co-localization was confirmed by calculating the Pearson coefficient, 0.6313 at a 41.65% colocalization rate (Figure 8c).…”
Section: ■ Results and Discussionmentioning
confidence: 95%